A device monitoring turbidity and color changes of beverages directly in bottled samples - Petr Gabriel; Karel Sigler (Kvasný průmysl, 2018)
Color and turbidity are important properties of fermented beverages, especially light and dark beers, white and red wines and spirits. The spectrum of absorption and scattering of light is a decisive and very important analytical parameter of the consumer's quality and health acceptability of the beverages. A large number of the above types of beverages are filled into transparent glass and plastic bottles that allow for optical measurements. The Colorturb prototype has been designed, developed and constructed to determine color changes and turbidity in commercial packaging. The device uses a red-green-blue (RGB) light-emitting diode as a light source to enable independent measurement of absorbance in the sample in 3 wavelength regions ranging up to 4 absorbance units. Absorbance measurement at 3 wavelengths makes it possible to eliminate the effect of the bottle color on the measurement and, apart from color intensity, to distinguish differences in the color hue of the samples.